Chondroitin Sulfate Alleviates Diabetic Osteoporosis and Repairs Bone Microstructure via Anti-Oxidation, Anti-Inflammation, and Regulating Bone Metabolism - Qi, Shan Shan; Shao, Meng Li; Sun, Ze; Chen, Si Min; Hu, Ying Jun; Li, Xin Sheng; Chen, De Jing; Zheng, Hong Xing; Yue, Tian Li (Frontiers in Endocrinology, 2021)
Diabetic osteoporosis (DOP) belongs to secondary osteoporosis caused by diabetes, it has the characteristics of high morbidity and high disability. In present study, we constructed type 1 diabetic rat model and administered chondroitin sulfate (200mg/kg) for 10 weeks to observe the preventive effect of chondroitin sulfate on the bone loss of diabetic rats. The results showed that chondroitin sulfate can reduce blood glucose and relieve symptoms of diabetic rats; in addition, it can significantly increase the bone mineral density, improve bone microstructure, and reduce bone marrow adipocytes number in diabetic rats; after 10 weeks chondroitin sulfate administration, the SOD activity level was up-regulated, as well as CAT levels, indicated that chondroitin sulfate can alleviate oxidative stress in diabetic rats; Chondroitin sulfate was also found can reduce the level of serum inflammatory cytokines (TNF-α, IL-1，IL-6, and MCP-1), and alleviate the inflammation in diabetic rats; bone metabolism markers detection results showed that chondroitin sulfate can reduce bone turnover in diabetic rats (decreased RANKL, CTX-1, ALP, and TRACP 5b levels were observed after 10 weeks chondroitin sulfate administration); At the same time, the bone OPG and RUNX 2 expression levels were higher after chondroitin sulfate treatment, the bone RANKL expression was lowered, and the OPG/RANKL ratio was up-regulated. All of those above indicated that chondroitin sulfate could prevent STZ induced DOP and repair bone microstructure, the main mechanism was through anti-oxidation, anti-inflammatory and regulating bone metabolism. Chondroitin sulfate could be used to develop anti-DOP functional foods and diet interventions for diabetes.